The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1021/acs.jmedchem.8b00373
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting Myeloid Differentiation Using Potent 2-Hydroxypyrazolo[1,5-a]pyridine Scaffold-Based Human Dihydroorotate Dehydrogenase Inhibitors

Abstract: Human dihydroorotate dehydrogenase ( hDHODH) catalyzes the rate-limiting step in de novo pyrimidine biosynthesis, the conversion of dihydroorotate to orotate. hDHODH has recently been found to be associated with acute myelogenous leukemia, a disease for which the standard of intensive care has not changed over decades. This work presents a novel class of hDHODH inhibitors, which are based on an unusual carboxylic group bioisostere 2-hydroxypyrazolo[1,5- a]pyridine, that has been designed starting from brequina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
90
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(97 citation statements)
references
References 64 publications
(139 reference statements)
7
90
0
Order By: Relevance
“…The inhibition of Dihydroorotate Dehydrogenase (DHODH) has recently been found to induce differentiation in several models of Acute Myeloid Leukemia (AML), both in vitro and in vivo [1]. From this seminal discovery, several academic and industrial research groups, including ours, have designed new and more potent DHODH inhibitors, confirming original results and extending the knowledge about this topic [2,3,4,5]. Transcriptome analyses revealed that leukemic cells treated with DHODH inhibitors upregulate genes related to apoptosis and differentiation, and downregulate protein translation-related genes, impairing protein synthesis [4,5].…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…The inhibition of Dihydroorotate Dehydrogenase (DHODH) has recently been found to induce differentiation in several models of Acute Myeloid Leukemia (AML), both in vitro and in vivo [1]. From this seminal discovery, several academic and industrial research groups, including ours, have designed new and more potent DHODH inhibitors, confirming original results and extending the knowledge about this topic [2,3,4,5]. Transcriptome analyses revealed that leukemic cells treated with DHODH inhibitors upregulate genes related to apoptosis and differentiation, and downregulate protein translation-related genes, impairing protein synthesis [4,5].…”
Section: Introductionsupporting
confidence: 58%
“…MEDS433 is a new, potent DHODH inhibitor, developed and characterized by our group, which can induce differentiation in multiple AML cell lines, at a 1-log lower concentration compared to brequinar [2]. Here we show that MEDS433 also has a strong apoptotic effect on several AML cell lines, again at a 1-log lower concentration compared to brequinar (Fig.…”
Section: Meds433 Induces Apoptosis In Several Aml Cell Linesmentioning
confidence: 56%
“…Recently, a series of hDHODH inhibitors were discovered by scaffold-hopping strategy or structural modification based on previous reported lead compounds [16,17] In our instance, the active compounds were selected based on in vitro screening. Our screening discovered a novel class of human DHODH inhibitors, which have a 6-isopropyl-1,5,6,7-tetrahydro-4Hbenzo[d] [1,2,3]triazol-4-one scaffold.…”
Section: A Novel Class Of Potent Inhibitors Of Human Dhodhmentioning
confidence: 99%
“…Chemical structures and in vitro inhibitory activities of human DHODH inhibitors. of teriflunomide is from the reference[17].…”
mentioning
confidence: 99%
“…Some pyrimidine biosynthesis inhibitors also exhibit broad-spectrum antiviral activity in vitro [1][2][3][17][18][19] and in vivo [20][21][22], opening new fields of application for this class of antimetabolites. In this context, the identification of novel DHODH inhibitors with original chemical and pharmacological properties has become a priority to overcome the limitations of existing molecules [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%